Analytical technologies for identification and characterization of the plant N-glycoproteome - Ruiz-May, Eliel; Thannhauser, Theodore W.; Zhang, Sheng; Rose, Jocelyn K. (Frontiers in Plant Science, 2012)
N-glycosylation is one of the most common and complex post-translational modifications of eukaryotic proteins and one that has numerous roles, such as modulating protein stability, sorting, folding, enzyme activity and ligand interactions. In plants, the functional significance of N-glycosylation is typically obscure, although it is a feature of most secreted proteins and so is potentially of considerable interest to plant cell wall biologists. While analytical pipelines have been established to characterize yeast, mammalian and bacterial N-glycoproteomes, such large-scale approaches for the study of plant glycoproteins have yet to be reported. Indeed, the N-glycans that decorate plant and mammalian or yeast proteins are structurally distinct and so modification of existing analytical approaches are needed to tackle plant N-glycoproteomes. In this review, we summarize a range of existing technologies for large-scale N-glycoprotein analysis and highlight promising future approaches that may provide a better understanding of the plant N-glycoproteome, and therefore the cell wall proteome and other proteins associated with the secretory pathway.